Screaming on the inside : the unsustainability of American motherhood - Grose, Jessica (Mariner Books, 2022)
"In this timely and necessary book, New York Times opinion writer Jessica Grose dismantles two hundred years of unrealistic parenting expectations and empowers today's mothers to make choices that actually serve themselves, their children, and their communities"--